Comparison of phytoncide with sirolimus as a novel drug candidate for drug-eluting stent - Kang, Sung Nam; Kim, Si-Eun; Choi, Jiyeon; Park, Kwideok; Goo, Jae Hwan; Sim, Doo Sun; Hong, Young Joon; Kim, Ju Han; Joung, Yoon Ki; Lee, Jay; Jeong, Myung Ho; Han, Dong Keun (ELSEVIER SCI LTD, 2015)
A drug-eluting stent (DES) is one of the commonly used treatment techniques in percutaneous coronary intervention (PCI). Sirolimus (SRL) has been widely used for DES as a drug for suppressing neointimal hyperplasia causing restenosis. Phytoncides (PTC) are compounds released from trees and plants, and their solutions contain monoterpenoids such as alpha-pinene, careen, and myrceen. Some studies have reported that these components exhibit antioxidant, antimicrobial, and anti-inflammatory activities. We hypothesized that PTC may become an alternative drug to SRL for DES, exhibiting alleviated side effects as compared to SRL. A PTC-incorporated stent was compared with an SRL-incorporated stent in terms of physicochemical, pharmacokinetic, and biological properties. In in vitro studies, the effects of each drug on cells were investigated. The results showed that both drugs exhibited similar cytotoxicity, antiinflammation, and antiproliferation effects. However, these effects resulted from different mechanisms associated with cells, as seen in the immunofluorescence result. An in vivo assay showed that the lumen area was significantly larger and the neointimal area was significantly smaller in SRL- and PTC-loaded stents compared to a drug-unloaded stent. These results suggest that phytoncide can be a feasible alternative drug to SRL for advanced DES although more studies are needed. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: CELL-DEATH; IN-VITRO; THROMBOSIS; RESTENOSIS; PACLITAXEL; REGULATORS; POLYMERS; DELIVERY; GROWTH; SPRAY